Preparation, Characterization And Properties Of Epoxy Particles Filled Epoxy Composites - Lim, Shu Bee (Universiti Sains Malaysia, 2017)
The objective of this study was to fabricate epoxy particle (EP) and to assess its potential to reinforced and toughened epoxy composites. Three sets of EP were produced by water-based emulsion method and characterized byusingField Emission Scanning Electron Microcopy (FESEM) Analysis, Particle Size Analysis and Brunauer-Emmett-Teller (BET) Surface Area Analysis. The samples for EP filled epoxy composite were prepared by incorporation of 5 wt% of EP into theepoxy matrix and cured at room temperature. Testing which werecarried out to investigate the mechanical properties of epoxy composites are Izod impact test, hardness and fracture toughness test. In addition, scanning electron microscope is used to analysis the fracture surface of the composite after fracture toughness failure. Thermal analysis of the epoxy composites is studied using differential scanning calorimetry and thermogravimetric analyzer. It was found that the incorporation of EP in epoxy matrix cause the reduction of mechanical properties such as reduction of minimum 19% in impact strength, reduction of minimum 0.95% in hardness and reduction of minimum 61% in fracture toughness. The reduction of mechanical properties is due to the poor interaction between EP and the epoxy matrix. The addition of the EP in theepoxy matrix also result in the decrement of the glass transition temperature (Tg) but not much different in term of thermal decomposition temperature.